[Incidentally diagnosed liver and right iliac muscle hydatid disease]. - Girgin, Mustafa; Kanat, Burhan Hakan; Ayten, Refik; Çetinkaya, Ziya (My University, 2012)
Hydatid cyst disease is localized in the liver and lungs in most of the cases, but also can exist throughout the body. In this article, we present a 20-year-old male patient who was diagnosed with hydatid cyst of the liver and iliac muscle, who presented because of respiratory problems. Especially in endemic areas, in patients who are detected as having hydatid cyst in the liver, systemic examinations must be cattied out and investigated regarding any involvement of other organs.
Rastlantisal Olarak Tani Konulmuş Karaci?er ve Sa? İliak Kas Kist Hidati?i.
Keywords: Echinococcosis; Echinococcosis, Hepatic; Humans; Incidental Findings; Male; Muscle, Skeletal; Muscular Diseases; Sacrococcygeal Region; Young Adult; adult; article; back; case report; echinococcosis; human; incidental finding; liver hydatid cyst; male; muscle disease; parasitology; skeletal muscle